Gene therapy and genome editing for type I glycogen storage diseases - Chou, Janice Y.; Mansfield, Brian C. (Frontiers in Molecular Medicine, 2023)
Type I glycogen storage diseases (GSD-I) consist of two major autosomal recessive disorders, GSD-Ia, caused by a deficiency in glucose-6-phosphatase-α (G6Pase-α or G6PC) and GSD-Ib, caused by a deficiency in the glucose-6-phosphate transporter (G6PT or SLC37A4). The G6Pase-α and G6PT are functionally co-dependent. Together, the G6Pase-α/G6PT complex catalyzes the translocation of G6P from the cytoplasm into the endoplasmic reticulum lumen and its subsequent hydrolysis to glucose that is released into the blood to maintain euglycemia. Consequently, GSD-Ia and GSD-Ib patients manifest a common metabolic phenotype of impaired glucose homeostasis and severe long-term risks of hepatocellular adenoma/carcinoma and renal disease. Rigorous dietary therapies have enabled GSD-I patients to maintain a normalized metabolic phenotype, but adherence is challenging. Moreover, dietary therapies do not address the underlying pathological processes, and long-term complications still occur in metabolically compensated GSD-I patients. Animal models of GSD-Ia and GSD-Ib have delineated the disease biology and pathophysiology, and guided development of effective gene therapy strategies for both disorders. Preclinical studies of GSD-I have established that recombinant adeno-associated virus (rAAV) vector-mediated gene therapy for GSD-Ia and GSD-Ib are safe, and efficacious. A phase III clinical trial of rAAV-mediated gene augmentation therapy for GSD-Ia (NCT05139316) is currently in progress. A phase I clinical trial of mRNA augmentation for GSD-Ia was initiated in 2022 (NCT05095727). Alternative genetic technologies for GSD-I therapies, such as gene editing, are also being examined for their potential to improve further long-term outcomes.